Penerapan School Based Inset Sebagai Upaya Meningkatkan Kemampuan Guru Dalam Melakukan Persiapan Dan Perencanaan Pembelajaran di Sdn 41/X Sungai Jambat Semester Genap Tahun Ajaran 2021/2022 - Pasman Pasman (Departement of Mathematics Education, 2023)
This study aims to obtain information and discuss the application of school-based inset as an effort to improve teachers' abilities in preparing and planning lessons at SDN 41/X Sungai Jambat even semester of the 2021/2022 academic year. This research is a school action research (PTS) which consists of two cycles by following the four stages of planning, implementing, observing and reflecting. This research was conducted at SDN 41/X Sungai Jambat in the even semester of the 2021/2022 school year with a total of 5 teacher subjects. Data was collected through observation sheets and documentation and analyzed using proportions and data reduction. Based on the results of the research and discussion, it can be interpreted that through the application of school-based inset, the teacher's ability to prepare and plan lessons at SDN 41/X Sungai Jambat even semester of the 2021/2022 academic year by giving rewards.